Implementasi Pendidikan Anti Korupsi Di Tingkat Menengah Atas Melalui Ekstrakulikuler - Kadek Yulia Pratiwi (Program Studi PPKn Universitas Pendidikan Ganesha, 2022)
The issues of corruption that are increasingly rife at this time require us to be able to self-reflect while continuing to carry out anti-corupption values. Anti-corupption valies carried out among educational units. This application can be in the from of activities carried out outside of class or extracurrucular hours as well as organozations that exist at the upper secondary level. In applying anti-corupption or what is called the fraud triangle, in this study using a type of descriptive aqualitive research with the method literature.